Utilisation of steel furnace slag coarse aggregate in a low calcium fly ash geopolymer concrete. (November 2016) - Khan, M.S.H.; Castel, Arnaud; Akbarnezhad, A.; Foster, Stephen J.; Smith, Marc
Abstract: This paper evaluates the performance of steel furnace slag (SFS) coarse aggregate in blended slag and low calcium fly ash geopolymer concrete (GPC). The geopolymer binder is composed of 90% of low calcium fly ash and 10% of ground granulated blast furnace slag (GGBFS). Mechanical and physical properties, shrinkage, and detailed microstructure analysis were carried out. The results showed that geopolymer concrete with SFS aggregate offered higher compressive strength, surface resistivity and pulse velocity than that of GPC with traditional aggregate. The shrinkage results showed no expansion or swelling due to delayed calcium oxide (CaO) hydration after 320 days. No traditional porous interfacial transition zone (ITZ) was detected using scanning electron microscopy, indicating a better bond between SFS aggregate and geopolymer matrix. Energy dispersive spectroscopy results further revealed calcium (Ca) diffusion at the vicinity of ITZ. Raman spectroscopy results showed no new crystalline phase formed due to Ca diffusion. X-ray fluorescence result showed Mg diffusion from SFS aggregate towards geopolymer matrix. The incorporation of Ca and Mg into the geopolymer structure and better bond between SFS aggregate and geopolymer matrix are the most likely reasons for the higher compressive strength observed in GPC with SFS aggregate.